Science, technology and innovation in the strategic programs of the Brazilian Navy - Israel de Oliveira Andrade; Mariana Carpes; Luiz Gustavo Aversa Franco; Giovanni Roriz Lyra Hillebrand (Institute for Applied Economic Research (ipea), 2022)
National Defense requires adequately trained, prepared and equipped armed forces to perform in guaranteeing national interests and protect sovereignty. Regarding the issue of equipping - which is the main focus of the three forces' (Navy, Army, and Air Force) strategic programs - it is not restricted to investment in updated defense equipment and systems procurement, but chiefly the development of endogenous scientific-technological capacities able to provide defense needs. This makes it vital to undertake efforts and investments in the area of science, technology, and innovation, especially in research and development activities aimed at national defense. The purpose of this work is to analyze the importance of such activities in the achievement of the main strategic programs of the Brazilian Navy. For this purpose, the main aspects of the interrelation between national defense and science, technology and innovation, the general characteristics of the Navy's main strategic programs and the importance of scientific-technological enterprises in their development will be examined.
Keywords: L64; O32; O38; 330; national defense; science; technology and innovation; Brazilian Navy; naval power; military technology; strategic programs; Brazilian Armed Forces